ANALISIS BUKU KELAS V SD/MI KURIKULUM 2013 PADA TEMA KERUKUNAN DALAM BERMASYARAKAT - Rima Trianingsih (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2016)
Various problems exist when the implementation of the curriculum of 2013. There is a mismatch between the content of the book with material and cognitive development of the students. This research is The Analysis of the Fifth Grade Book SD/MI of the Curriculum 2013 on the Theme Kerukunan dalam Bermasyarakat. The purpose of this study is to describe how the suitability of the content, the presentation and the language on the fifth grade book of the theme kerukunan dalam bermasyarakat. The methods used in this research is descriptive qualitative research methods. Type a descriptive qualitative research used in this study is the analysis of contents or document. The results showed that seen from the aspect of the material, there is still a mismatch between the activities with the theme, the development of cognitive students and the steps of scientific approach. Seen from the presentation is good, coherently, complete with a themes macth with daily life. But the activities must more contextual. Seen of the language, there are several paragraphs that are not true because between paragraphs 1 and 2 not macth with the context of the talks. The paragraph is coherent and effective, use of the language structure is macth with the child language development.